2021
DOI: 10.2196/29074
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Family Caregivers’ Use of Their Adult Care Recipient’s Patient Portal From the 2019 Health Information National Trends Survey: Secondary Analysis

Abstract: Background Patient engagement is critical for realizing the value of telehealth modalities such as the patient portal. Family caregiver engagement may also be critical for facilitating the use of the patient portal among adult patients, including older adults. Objective This study aims to analyze the 2019 Health Information National Trends Survey to characterize family caregivers’ use of their care recipient’s patient portal in terms of sociodemographic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Greater health literacy and educational level (5 of 8 articles), 25 , 26 , 45 , 52 , 53 female gender (5 articles), 25 , 45 , 47 , 48 , 54 and being a family member (6 articles) 25 , 26 , 42 , 45 , 47 , 53 were facilitators of care partner use of the portal. Evidence regarding care partner race (5 articles) 25 , 45 , 53 , 54 , 55 and household income (5 articles) 21 , 25 , 45 , 53 , 55 was mixed. Two articles 26 , 54 examined care partners’ use of their own portal and both found it to be a facilitator.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater health literacy and educational level (5 of 8 articles), 25 , 26 , 45 , 52 , 53 female gender (5 articles), 25 , 45 , 47 , 48 , 54 and being a family member (6 articles) 25 , 26 , 42 , 45 , 47 , 53 were facilitators of care partner use of the portal. Evidence regarding care partner race (5 articles) 25 , 45 , 53 , 54 , 55 and household income (5 articles) 21 , 25 , 45 , 53 , 55 was mixed. Two articles 26 , 54 examined care partners’ use of their own portal and both found it to be a facilitator.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence regarding care partner race (5 articles) 25 , 45 , 53 , 54 , 55 and household income (5 articles) 21 , 25 , 45 , 53 , 55 was mixed. Two articles 26 , 54 examined care partners’ use of their own portal and both found it to be a facilitator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training on portals among patients and caregivers can encourage use and dispel concerns about technology and security risks. Allowing patients to set boundaries on what information can be accessed by caregivers will also be important for protecting patient privacy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electronic health records (EHR) were designed to safely store transactional patient information and increase communication among healthcare team members (1). Over time, patient-facing EHR portals invited patients to access their health information remotely and communicate with healthcare providers securely (29). A secondary analysis of the 2019 Health Information National Trends Survey found that more than 55% of patients use a portal to access their health record electronically (3).…”
mentioning
confidence: 99%